20(S)-ginsenoside Rh2 as agent for the treatment of LMN-CRC via regulating epithelial–mesenchymal transition. Issue 3 (25th March 2020) - Yuan, Yihang; Wang, Jue; Xu, Ming; Zhang, Yunpeng; Wang, Zhiqiang; Liang, Leilei; Sun, Peng
Abstract: The lymph node metastasis of colorectal cancer (LMN-CRC) seriously threatens the prognosis of patients. Chemotherapy, as the most common treatment, results in severe bone marrow suppression. 20(S)-ginsenoside Rh2 (SGRh2), a major effective constituent of ginseng, has demonstrated therapeutic effects on a variety of diseases, including some tumours. SGRh2 treatment had no effect on other organs. Therefore, ginsenosides are considered a safe and effective antineoplastic drug. However, the effects of SGRh2 on LMN-CRC remain unknown. The present study investigated the potential effect of SGRh2 on LMN-CRC in vitro and in vivo . SW480 and CoLo205 cell lines were treated with SGRh2. SGRh2 dose-dependently decreased CRC cell proliferation by CCK-8, colony formation and Edu assays. The Transwell and scratch assays revealed that SGRh2 inhibits the migratory and invasive abilities of CRC cells in a dose-dependent manner. Furthermore, the results of Western blotting revealed that SGRh2 decreased the expression of matrix metalloproteinase (MMP)-2 and MMP9. In terms of the underlying mechanisms, SGRh2 regulates CRC metastasis by affecting epithelial–mesenchymal transition (EMT), which significantly up-regulated epithelial biomarkers (E-cadherin) and down-regulated mesenchymal biomarkers (N-cadherin and vimentin) and EMT transcriptional factors (Smad-3, Snail-1, and Twist-1). In vivo, SGRh2 significantly inhibited LMN-CRC without affecting other normal organs. Immunohistochemical results showed that SGRh2 treats LMN-CRC by regulating EMT. These results demonstrate that SGRh2 has therapeutic potential for LMN-CRC.